Bipartite graphs with at most six non-zero eigenvalues - Oboudi, Mohammad Reza (Ars mathematica contemporanea, 2016)
In this paper we characterize all bipartite graphs with at most six non-zero eigenvalues. We determine the eigenvalues of bipartite graphs that have at most four nonzero eigenvalues.
Keywords: bipartite graphs; dvodelni grafi; eigenvalues of graphs; lastne vrednosti grafov